PENAFSIRAN PANCASILA DALAM PERSPEKTIF ISLAM: PETA KONSEP INTEGRASI - Ridwan, MK (IAIN Ponorogo, 2017)
Abstract: Indonesia as a pluralism nation-state has established Pancasila as the state ideology. Pancasila is the result of the conceptualization and history of the struggle of the Indonesian. It contains the noble values and keeps the spirit of the nation's struggle. Due to the failures of the government in developing the country, radical groups appeared for replacing Pancasila ideology into Islamic Shari'a. They claims that Pancasila along with three other pillars as the ideology of